A walk through the development of human leukocyte antigen typing: from serologic techniques to next-generation sequencing - Haeyoun Choi; Eun-Jeong Choi; Hyoung-Jae Kim; In-Cheol Baek; Aegyeong Won; Su Jin Park; Tai-Gyu Kim; Yeun-Jun Chung (Clinical Transplantation and Research)
Human leukocyte antigen (HLA) is a group of glycoproteins encoded by the major histocompatibility complex (MHC) that plays a pivotal role in the host's immune defense. Given that the MHC represents the most polymorphic region in the human genome, HLA typing is crucial in organ transplantation. It significantly influences graft rejection, graft-versus-host disease, and the overall patient outcome by mediating the discrimination between self and nonself. HLA typing technology began with serological methods and has evolved rapidly alongside advances in molecular technologies, progressing from DNA-based typing to next- or third-generation sequencing. These advancements have increased the accuracy of HLA typing and reduced ambiguities, leading to marked improvements in transplantation outcomes. Additionally, numerous novel HLA alleles have been identified. In this review, we explore the developmental history and future prospects of HLA typing technology, which promises to further benefit the field of transplantation.